Still births, neonatal deaths and neonatal near miss cases attributable to severe obstetric complications: a prospective cohort study in two referral hospitals in Uganda - Nakimuli, Annettee; Mbalinda, Scovia N.; Nabirye, Rose C.; Kakaire, Othman; Nakubulwa, Sarah; Osinde, Michael O.; Kakande, Nelson; Kaye, Dan K. (BMC pediatrics, 2015)
Neonatal near miss cases occur more often than neonatal deaths and could enable a more comprehensive analysis of risk factors, short-term outcomes and prognostic factors in neonates born to mothers with severe obstetric complications. The objective was to assess the incidence, presentation and perinatal outcomes of severe obstetric morbidity in two referral hospitals in Central Uganda. Methods: A prospective cohort study was conducted between March 1, 2013 and February 28, 2014, in which all newborns from cases of severe pregnancy and childbirth complications were eligible for inclusion. The obstetric conditions included obstetric haemorrhage, hypertensive disorders, obstructed labour, chorioamnionitis and pregnancy-specific complications such as malaria, anemia and premature rupture of membranes. Still births, neonatal deaths and neonatal near miss cases (defined using criteria that employed clinical features, presence of organ-system dysfunction and management provided to the newborns were compiled). Stratified and multivariate logistic regression analysis was conducted to identify risk factors for perinatal death. Results: Of the 3100 mothers, 192 (6.2%) had abortion complications. Of the remainder, there were 2142 (73.1%) deliveries, from whom the fetal outcomes were 257 (12.0%) still births, 369 (17.2%) neonatal deaths, 786 (36.7%) neonatal near misses and 730 (34.1%) were newborns with no or minimal life threatening complications. Of the 235 babies admitted to the neonatal intensive care unit (NICU), the main reasons for admission were prematurity for 64 (26.8%), birth asphyxia for 59 (23.7%), and grunting respiration for 26 (11.1%). Of the 235 babies, 38 (16.2%) died in the neonatal period, and of these, 16 died in the first 24 hours after admission. Ruptured uterus caused the highest case-specific mortality of 76.8%, and led to 16.9% of all newborn deaths. Across the four groups, there were significant differences in mean birth weight, p = 0.003. Conclusions: Antepartum hemorrhage, ruptured uterus, severe preeclampsia, eclampsia, and the syndrome of Hemolysis, Elevated Liver Enzymes, Low Platelets (HELLP syndrome), led to statistically significant attributable risk of newborn deaths (still birth or neonatal deaths). Development of severe maternal outcomes, the mothers having been referred, and gravidity of 5 or more were significantly associated with newborn deaths.
Keywords: Neonatal near; Still births; neonatal deaths